Carpentier, Alejo (2013). Diary (1951-1957). Armando Raggi, Ed. Cuba: Biblioteca Alejo Carpentier/Editorial Letras Cubanas. A Review by Marlene Vázquez - Vazquez-Pérez, Marlene (2015)
Professor Marlene Vazquez presents her review on Armando Raggi's annotated edition of Alejo Carpentier's Diary.  Carpentier kept a Diary from 1951 to 1957. Mr. Raggi's edition was lauched during the Book Fair of La Habana on 2014.  This edition, as Professor Vazquez states, is essential for scholars and for people interested in studying Carpentier's works.